A 3-day low-fibre diet does not improve colonoscopy preparation results compared to a 1-day diet: A randomized, single-blind, controlled trial. Issue 10 (December 2019) - Taveira, Filipe; Areia, Miguel; Elvas, Luís; Alves, Susana; Brito, Daniel; Saraiva, Sandra; Cadime, Ana T
Background: Although a 1-day low-fibre diet before colonoscopy is currently recommended, some endoscopists prescribe a 3-day diet. Objective: The objective of this study was to compare the influence of a 3-day versus a 1-day low-fibre diet on bowel preparation quality, patient tolerability and adherence. Methods: Outpatients scheduled for total colonoscopy were randomized in two groups, 3-day versus 1-day low-fibre diet, performing a 4-litre polyethylene glycol split-dose. The primary outcome was a reduction of inappropriate preparations in the 3-day low-fibre diet arm from 15% to 5% (bowel preparation was assessed by the Boston Bowel Preparation Scale). Secondary outcomes were adherence to, difficulty to perform, difficulty to obtain and willingness to repeat the diet. Intention-to-treat (ITT) and per-protocol (PP) analyses were conducted for the primary outcome. Results: A total of 412 patients were randomized (206 per group). Bowel preparation quality was similar between groups. On ITT analysis ( n  = 412), adequate bowel preparation was 91.7% (3-day diet) versus 94.7% (1-day diet), p  = 0.24 and on PP analysis ( n  = 400) 93.5% versus 96.5%, respectively, p  = 0.16. Difficulty to perform the diet was significantly higher on the 3-day diet, p  = 0.04. No differences were found on difficulty to obtain the diet, willingness to repeat the diet, adverse events and intra-colonoscopy findings. Conclusion: A 3-day low-fibre diet does not bring benefit to the bowel preparation quality and is harder to perform than a 1-day diet.